Artificial antigen‐presenting cells expressing HLA class II molecules as an effective tool for amplifying human specific memory CD4+ T cells. Issue 7 (26th April 2016) - Garnier, Anthony; Hamieh, Mohamad; Drouet, Aurélie; Leprince, Jérôme; Vivien, Denis; Frébourg, Thierry; Le Mauff, Brigitte; Latouche, Jean‐Baptiste; Toutirais, Olivier
Abstract : Owing to their multiple immune functions, CD4 + T cells are of major interest for immunotherapy in chronic viral infections and cancer, as well as for severe autoimmune diseases and transplantation. Therefore, standardized methods allowing rapid generation of a large number of CD4 + T cells for adoptive immunotherapy are still awaited. We constructed stable artificial antigen‐presenting cells (AAPCs) derived from mouse fibroblasts. They were genetically modified to express human leukocyte antigen (HLA)‐DR molecules and the human accessory molecules B7.1, Intercellular adhesion molecule‐1 (ICAM‐1) and lymphocyte function‐associated antigen‐3 (LFA‐3). AAPCs expressing HLA‐DR1, HLA‐DR15 or HLA‐DR51 molecules and loaded with peptides derived from influenza hemagglutinin (HA), myelin basic protein (MBP) or factor VIII, respectively, activated specific CD4 + T‐cell clones more effectively than Epstein‐Barr virus (EBV)‐transformed B cells. We also showed that AAPCs were able to take up and process whole Ag proteins, and present epitopes to specific T cells. In primary cultures, AAPCs loaded with HA peptide allowed generation of specific Th1 lymphocytes from healthy donors as demonstrated by tetramer and intracellular cytokine staining. Although AAPCs were less effective than autologous peripheral blood mononuclear cells (PBMCs) to stimulate CD4 + T cells in primary culture, AAPCs were more potent to reactivate and expand memory Th1 cells in a strictly Ag‐dependent manner. As the availability of autologous APCs is limited, the AAPC system represents a stable and reliable tool to achieve clinically relevant numbers of CD4 + T cells for adoptive immunotherapy. For fundamental research in immunology, AAPCs are also useful to decipher mechanisms involved in the development of human CD4 T‐cell responses.